2017
DOI: 10.1111/cea.12995
|View full text |Cite
|
Sign up to set email alerts
|

Association between infection with Helicobacter pylori and atopy in young Ethiopian children: A longitudinal study

Abstract: These data are consistent with the hypothesis that early exposure to H. pylori is inversely associated with atopy and allergic conditions. A possible modest protective association against atopy was observed in those infected with a more virulent CagA+ strain of H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
7
13
0
1
Order By: Relevance
“…From an epidemiologic point of view, Fouda et al, who studied 90 asthmatic children and 90 healthy controls, reported a significantly lower prevalence of H. pylori in the first group (25.6% vs 44.4%) and an inverse correlation between asthma and anti‐ H. pylori IgG titers . Similar results were reported by Taye et al, who enrolled 856 Ethiopian children in their study, showing an inverse relationship between H. pylori infection, CagA positivity, and both atopy and allergic asthma . Even a meta‐analysis of data from 24 studies enrolling 1247 patients and 2410 controls by Chen et al reported an inverse relationship between H. pylori infection (OR: 0.83; 95% CI: 0.71, 0.98), CagA positivity (OR: 0.77; 95% CI: 0.66, 1.78), and allergic asthma .…”
Section: Respiratory Diseasessupporting
confidence: 56%
“…From an epidemiologic point of view, Fouda et al, who studied 90 asthmatic children and 90 healthy controls, reported a significantly lower prevalence of H. pylori in the first group (25.6% vs 44.4%) and an inverse correlation between asthma and anti‐ H. pylori IgG titers . Similar results were reported by Taye et al, who enrolled 856 Ethiopian children in their study, showing an inverse relationship between H. pylori infection, CagA positivity, and both atopy and allergic asthma . Even a meta‐analysis of data from 24 studies enrolling 1247 patients and 2410 controls by Chen et al reported an inverse relationship between H. pylori infection (OR: 0.83; 95% CI: 0.71, 0.98), CagA positivity (OR: 0.77; 95% CI: 0.66, 1.78), and allergic asthma .…”
Section: Respiratory Diseasessupporting
confidence: 56%
“…Interestingly, there is proof suggesting H pylori infection in fetus period may have beneficial effect. Two cohort studies provided further evidence that exposure to H pylori infection in fetal life played a protective role in the development of atopy and allergy. Inflammatory response induced by H pylori is relevant with Th1‐mediated cellular response, and the protective effect of H pylori against atopy and allergy is also mediated by secretion of regulatory T cell .…”
Section: Discussionmentioning
confidence: 99%
“…Their main finding was that H. pylori infection, at any age up to 6.5 years, was associated with a lower prevalence of both atopy and any allergic condition (adjusted OR: 0.54 [95% CI: 0.32‐0.92] and 0.31 [95% CI: 0.10‐0.94], respectively). Although the authors concluded that early exposure to H. pylori was inversely associated with atopy and allergic conditions, H. pylori infection at the age of 6.5 years was inversely related to the prevalence of atopy but not significantly . This supports data from a smaller case‐control study showing a nonsignificant lower H. pylori positivity among children with allergies compared with individuals without allergies: 13.9% (17/122) vs 22.4% (22/98), respectively .…”
Section: Clinical Manifestationsmentioning
confidence: 60%
“…Ireland over a long-term follow-up period. They identified H. pylorinegative children (n = 210) in a study from 1997 to 2001 and determined their current H. pylori status by 13 C urea breath test (UBT). In addition, they also investigated the family members (n = 626), including younger siblings (n = 75), who were not included in the first study.…”
Section: Studied H Pylori Incidence Inmentioning
confidence: 99%